Extended first-trimester screening using multiple sonographic markers and maternal serum biochemistry: a five-year prospective study. - Hsiao, Ching-Hua; Cheng, Po-Jen; Shaw, S W Steven; Hsu, Jenn-Jeih; Chen, Ran-Chou; Tseng, Yin-Jiun; Chu, Woei-Chyn (Fetal Diagnosis & Therapy, 2014)
Objective: To examine the performance of first-trimester screening test combining several fetal sonographic and maternal biochemical markers for major aneuploidy in a Chinese population. Methods: This was a prospective study performed over 5 years between January 2005 and December 2010 in Taiwan, with 20,586 cases that had a combination of a variety of sonographic markers and maternal serological β-human chorionic gonadotropin and pregnancy-associated plasma protein-A levels assessed at first trimester screening between 11(+0) and 13(+6) weeks of gestation. The risk of aneuploidy was calculated using algorithm software developed by Fetal Medicine Foundation, London. Fetal karyotyping was performed when the prenatal screening showed a risk of 1/300 or higher. All cases were followed for fetal outcome. Results: The study population was divided into four groups according to the screening strategy performed. The combination of maternal serological biochemistry and nuchal translucency measurement had a 66.7% detection rate of trisomy 21. Addition of nasal bone status increased the detection rate of trisomy 21 to 88.2%. Inclusion of tricuspid regurgitation flow showed an 87.5% detection rate of trisomy 21. Further inclusion of ductus venosus flow increased the detection rate of trisomy 21 to 100%. Incorporating more markers greatly increased the detection rate and decreased the false-positive rate (FPR). Conclusion: Extension of first-trimester screening to include more sonographic markers greatly increased the sensitivity and decreased FPR for detection of chromosomal abnormalities. Such screening strategy is effective in clinical practice for the Chinese ethnic population.